(untitled) (Mongolian Journal of Chemistry, 2020)
The polysaccharides isolated from Polygonatum odoratum (Mill.) Druce (POPs) by water extraction, after precipitation with ethanol were purified through deproteinization, decolorization, dialysis, and column chromatography leading to a purified polysaccharide (POPs-I) content of 90.7 %. The scavenging of oxygen free radicals and inhibition of lipid peroxidation (LPO) by POPs-I were analyzed using a colorimetric method. The results showed that the hydroxyl radical scavenging ability of the polysaccharides was weaker than that of benzoic acid, but stronger than those of ascorbic acid and mannitol, and that the superoxide anion radical scavenging ability was inferior to those of all three. When the concentration was higher than 1.0 mg/mL, the POPs-I could inhibit LPO by superoxide anion radicals to a certain degree. Therefore, this work suggests that POPs-I are potential antioxidant agents in medicine and functional food.